The cycle of violence in the socio-educational system: from the myth to the fallacy of socio-education - Bonalume, Bruna Carolina; Jacinto, Adriana Giaqueto (Argumentum, 2020)
This article develops a critical reflexive analysis of the tensions and contradictions that currently crisscross socio-education. It addresses the manifestations of violence perpetuated by the State bodies that control the punitive pathway directed at adolescents and young people who commit infractions, including the Socio-Educational system. It results from qualitative social research, based on historical dialectical materialism, and adopts, as a methodological strategy for data collection, in-depth interviews with eight young people who were exposed to socio-educational measures in an open environment. We conclude that institutional violence is one of the barbaric forms that permeate the Brazilian socio-educational system and lends itself more to being incorporated into a penal system than a system that guarantees rights.Keywords: Socio-education. State. Socio-penal Control. Violence.